Summer Abundance of Harbour Porpoises (Phocoena phocoena) in the Coastal Waters of Iceland and the Faroe Islands - Anita Gilles; Thorvaldur Gunnlaugsson; Bjarni Mikkelsen; Daniel G. Pike; Gísli A. Víkingsson (NAMMCO Scientific Publications, 2020)
This study presents the first fully corrected abundance estimates for the harbour porpoise (Phocoena phocoena) for Iceland and the Faroe Islands. In both regions reliable estimates are needed to assess the impact of by-catch and other threats to harbour porpoises. Aerial surveys with harbour porpoise as a secondary and main target species were conducted in the summers of 2007 and 2010 in Icelandic and in Faroese coastal waters respectively. In Iceland, the cue counting procedure was used (which also produces the data required for line transect analysis), while in the Faroese, standard line transect sampling was applied, following the SCANS-II (Small Cetacean Abundance in the North Sea) survey protocol. In both surveys, identical aircraft surveyed at an altitude of 600 ft and a speed of 90–100 kn. Only data collected during Beaufort Sea States (BSS) lower than 3 and during good or moderate porpoise sighting conditions were used for abundance estimates. Abundance estimates were corrected using stratified estimates of esw (incorporating g(0)) values derived during the SCANS-II survey in 2005 as principal observers took part in this survey as well. In Iceland, realised effort in good or moderate harbour porpoise sighting conditions totalled 8,289 km in 13 survey strata, where 77 sightings (109 individuals) were made by the experienced harbour porpoise observer only. In Faroese waters, only part of the area inside the 300 m depth curve could be surveyed and 1,564 km were surveyed in good or moderate porpoise sighting conditions, yielding 39 sightings (49 individuals). The total abundance estimates were 43,179 porpoises (CV=0.45; 95% CI: 31,755–161,899) for Icelandic coastal waters and 5,175 porpoises (CV=0.44; 95% CI: 3,457–17,637) for Faroese waters.